DEVELOPMENT OF A VIRTUAL LABORATORY AS A LEARNING SUPPORT MEDIA TO IMPROVE BIOLOGY LEARNING OUTCOMES OF HIGH SCHOOL STUDENTS - Kamilia Fadhilah Maryana; Rusdi Rusdi; Ratna Komala (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2024)
Practicum is one of the activities that has become a characteristic of Biology. Students have good learning experiences and concepts through practical activities. In the Excretory System material at high school level, there are obstacles in practical activities because the research samples used are limited and require special treatment. Learning media such as virtual laboratories expected can overcome these obstacles. This research aims to: (a) develop media in the form of a virtual laboratory on Excretory System material, (b) test the product so that the product is suitable for use, and (c) analyze the application of the product in improving student learning outcomes. This development research using the ADDIE model, which consists of five stages (Analyze, Design, Development, Implementation, Evaluation) are chosen in this study. The validation from the expert uses three experts, and for the user evaluation, this study uses 50 students as the respondent. The research results show that the feasibility test by experts is included in the valid category. The results of hypothesis testing show that there is an increase in student learning outcomes before and after using virtual laboratory media. The N-gain calculation result of 0.53 is categorized in the medium category. Based on the results of product validation and application, it is concluded that the Excretory Systems Virtual Laboratory is suitable as an interactive support learning media and can improve the learning outcomes of high school students.